The brain structure underlying the nonlinear association between early-life tobacco smoke exposure and the risk for cognitive decline and dementia in adulthood: a large prospective cohort study - Changfu Lin; Fabin Lin; Kaitai Yang; Yuxuan Zhong; Yan Luo; Hanchen Chen; Wenjing Zhang; Xuanjie Chen; Qinyong Ye; Yuqi Zeng; Guoen Cai (BMC Public Health)
Abstract Background The impacts of early-life tobacco smoke exposure, including exposure during pregnancy and the initiation of smoking during childhood and adolescence, on cognitive decline and the risk of dementia in later life have not been investigated. Methods We used data from the UK Biobank (UKB) to assess early-life tobacco exposure, including in utero exposure and the age at which smoking was initiated. Cox proportional-hazards regression models were employed to gauge the relationships between early-life tobacco smoke exposure and both the risk of cognitive decline and dementia in adulthood. We adjusted for potential confounding factors, including age, gender, race, household income, alcohol consumption status, physical activity, family history of dementia, education level, and other relevant variables. Results This study of 291,113 UKB participants and 4,836 new dementia cases over a median 13.26-year follow-up found that in utero tobacco exposure led to significant cognitive decline in adulthood, but not a higher dementia risk. Those who began smoking in childhood or adolescence had significant cognitive decline and increased dementia risk. Early smoking was linked to various brain structure changes, including volumes of the hippocampus, lateral ventricles, white and gray matter. Conclusions Early exposure to tobacco is associated with cognitive decline and an increased risk of dementia in adulthood. This underscores the significance of educational campaigns targeting the reduction of smoking among children, adolescents, and pregnant women as an effective strategy to mitigate cognitive decline and dementia in adulthood.